2008
DOI: 10.1002/rcm.3487
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotopes to unravel and predict the origins of great cormorants (Phalacrocorax carbo sinensis) overwintering at Kinmen

Abstract: The Food and Agricultural Organization of the United Nations and the World Organization for Animal Health have called for a better understanding of the role that migrating birds may play in spreading H5N1 highly pathogenic avian influenza (HPAI). Bird banding, traditionally used in studies of migration, is limited by low recapture rates. Telemetry can only be applied to larger species and a limited number of birds. We show that analyses of multiple stable isotopes (delta(13)C, delta(15)N, delta(18)O and deltaD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Combining isotopic signatures of feathers with knowledge of moult patterns has allowed the reconstruction of migration routes (Ramos et al 2009a), provided information on the possible transmission of the H5N1 strain of avian influenza (Chang et al 2008; Horacek 2011), and revealed variation in habitat preferences both within and between species during the nonbreeding period (Cherel et al 2006; Phillips et al 2009). This has enabled the migratory patterns and habitat selection of individuals during the winter to be linked to subsequent condition and breeding performance (Marra et al 1998; Furness et al 2006; Inger et al 2008) and identifies the geographical origins of pollutant burdens carried by seabirds (Leat et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Combining isotopic signatures of feathers with knowledge of moult patterns has allowed the reconstruction of migration routes (Ramos et al 2009a), provided information on the possible transmission of the H5N1 strain of avian influenza (Chang et al 2008; Horacek 2011), and revealed variation in habitat preferences both within and between species during the nonbreeding period (Cherel et al 2006; Phillips et al 2009). This has enabled the migratory patterns and habitat selection of individuals during the winter to be linked to subsequent condition and breeding performance (Marra et al 1998; Furness et al 2006; Inger et al 2008) and identifies the geographical origins of pollutant burdens carried by seabirds (Leat et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations utilizing satellite tracking devices have not unequivocally linked HPAI in wild birds with the infections occurring in poultry. Hence, there have been recommendations that SIA should be added to banding and satellite tracking technologies as part of the surveillance strategy for HPAI (Chang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The values of δ 2 H in actively growing feathers agreed with those expected from the isotopic values found in the collection sites. There is still need to improve the data on δ 2 H isoscapes in the region as these are not well described at present (Chang et al 2009) as well as development of a feather collection protocol to standardize sampling efforts and develop an Asian δ 2 H feather isoscape base map (Pérez et al 2010). Stable hydrogen isotope analysis has also been used to determine the biogeography of avian hematozoan infections caused by Leucocytozoon and Haemoproteus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Although Asia is a prime focus for HPAI, and despite considerable interest in conservation and disease surveillance issues involving waterbirds in that region investigations on migratory connectivity in wild birds that might be implicated in the spread of the disease are few (Chang et al 2008 ;Pérez et al 2010 ). The great cormorant ( Phalacrocorax carbo sinensis ) is a potential carrier of HPAI to Taiwan and to better understand the migration of this bird, SIA studies were conducted on several populations from different breeding sites and overwintering grounds (Chang et al 2008 ).…”
Section: Determining Migratory Connectivity For Waterfowl In Asiamentioning
confidence: 99%